A Belgian flat income tax: Effects on labour supply and income distribution - André Decoster; Kris De Swerdt; Kristian Orsini (University of Essex, Institute for Social and Economic Research (ISER), 2008)
The adverse distributional effects of a flat tax are well known and have been documented by empirical research in several countries, including Belgium. Advocates of the flat tax argue, correctly, that many of these studies do not take into account agents' behavioural reactions and possible feed back effects. One of the important effects in this context is the potential increase in labour supply and the resulting increase in the taxable base and decrease in unemployment allowances. In this study we calculate the cost recovery based on a micro-simulation model that includes a labour supply model. We find that there is indeed a clearly positive effect on labour supply and hence also on the tax base. By introducing a revenue-neutral flat tax, labour supply increases by approximately 47,000 full-time equivalents. However, the effect is limited because, compared to a static scenario, the cost recovery only allows the revenue-neutral flat tax to decrease from 38.5% to 37%. Furthermore, there is little or no impact of these employment effects on the strongly regressive nature of a flat tax reform.
Keywords: C81; D31; H22; H24; J22; 330; flat tax; income distribution; microsimulation; labour supply; Einkommensverteilung; Flat Tax; Arbeitsangebot; Steueraufkommen; Belgien